The Impact of Emotional Intelligence on Developing Creativity Engines among Students of Al-Darb Community College in Dhamar Governorate – Yemen - Qaied Abdullah Abdurrahman Alsadaee (University of Science and Technology, Sana’a, Yemen, 2024)
The study aimed to investigate the impact of emotional intelligence with its dimensions (managing emotions, using emotions, self-motivation, self-awareness, and social communication) on developing creativity engines with their dimensions (embracing creativity, orientation towards learning and knowledge, and mental and psychological qualities). The study employed the descriptive analytical approach. The study population consisted of all students of Al-Darb Community College in Dhamar Governorate – Yemen, whereas the study sample amounted to (193) students from various academic levels and specializations. A questionnaire was used as a data collection tool, and the Statistical Package for the Social Sciences (SPSS version 28) was utilized for analyzing and processing data as well as testing the study hypotheses. The study found an impact of emotional intelligence on developing creativity engines. Moreover, all emotional intelligence dimensions except “using emotions” showed a significant impact on developing creativity engines.